International incidents : the law that counts in world politics - Reisman, W. Michael (William Michael), 1939-; Willard, Andrew R.; Yale Law School (Princeton, New Jersey : Princeton University Press, 1988)
What law "counts" in international politics? Does any? How are effective international norms established? This provocative book introduces a new way of looking at these questions. It shows that many international standards of acceptable conduct derive far less from adjudications, statutes, or treaties and far more from what is found to be acceptable in the conflicts that we today call international incidents. The contributors demonstrate how law that counts has been developed, modified, and terminated in a variety of dramatic international incidents: the Cosmos 954 satellite accident, the downing of Korean Air Lines Flight 007, the Harrods bombing, the Argentine invasion of the Falklands/Las Malvinas, the incursions of foreign submarines into Swedish waters, the Soviet gas pipeline problem, the situation in Lebanon, and the Gulf of Sidra incident. This volume is a first, experimental effort at establishing a format for a new and more relevant kind of international political and legal analysis. Originally published in 1988. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905
Frontmatter -- Contents -- Preface and Acknowledgments -- Contributors -- 1. International Incidents: introduction to a New Genre in the Study of International Law / Reisman, W. Michael -- 2. Incidents: An Essay in Method / Willard, Andrew R. -- 3. Foreign Submarines in Swedish Waters: The Erosion of an International Norm / Sadurska, Romana -- 4. Cosmos 954: The International Law of Satellite Accidents / Cohen, Alexander F. -- 5. The Soviet Gas Pipeline Incident: Extension of Collective Security Responsibilities to Peacetime Commercial Trade / Desouza, Patrick J. -- 6. The Argentine Invasion of the Falklands: International Norms of Signaling / Socarras, Michael P. -- 7. The War in Lebanon: The Waxing and Waning of International Norms / Hufford, D. Brian ; Malley, Robert -- 8. The Gulf of Sidra Incident of 1981: The Lawfulness of Peacetime Aerial Engagements / Ratner, Steven R. -- 9. The Shooting of Korean Air Lines Flight 007: Responses to Unauthorized Aerial Incursions / Morgan, Craig A. -- 10. The Bombing of Harrods: Norms against Civilian Targeting / Kuerbitz, Ronald J. -- 11. The Study of Incidents: Epilogue and Prologue / Reisman, W. Michael ; Willard, Andrew R. -- Index.
Papers originally presented at the Yale Law School Spring 1984 seminar The incident as a decision unit in international law.
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: International relations -- Congresses; International law -- Congresses; World politics -- 1945-1989 -- Congresses; Relations internationales -- Congrès.; Politique mondiale -- 1945-1989 -- Congrès.; LAW -- International; International law; International relations; World politics; 1945-1989; Conference papers and proceedings